2011
DOI: 10.1116/1.3622619
|View full text |Cite
|
Sign up to set email alerts
|

Phase, grain structure, stress, and resistivity of sputter-deposited tungsten films

Abstract: Residual stress, microstructure, and structure of tungsten thin films deposited by magnetron sputtering Sputter-deposited W films with nominal thicknesses between 5 and 180 nm were prepared by varying the base pressure prior to film deposition and by including or not including sputtered SiO 2 encapsulation layers. X-ray and electron diffraction studies showed that single phase, polycrystalline a-W could be achieved in as-deposited films as thin as 5 nm. The stress state in the as-deposited films was found to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
52
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(61 citation statements)
references
References 38 publications
7
52
1
1
Order By: Relevance
“…Sputtering power was fixed at 250 W. The deposition rate at this power was 1.4 Å/sec. Following deposition, the films were annealed at 850°C for two hours in Ar + 4% H 2 ambient19.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sputtering power was fixed at 250 W. The deposition rate at this power was 1.4 Å/sec. Following deposition, the films were annealed at 850°C for two hours in Ar + 4% H 2 ambient19.…”
Section: Methodsmentioning
confidence: 99%
“…S4] Film thicknesses were measured by X-ray reflectivity. Film resistivities were measured using the van der Pauw method121920.…”
Section: Methodsmentioning
confidence: 99%
“…1(j)) corresponds to the structural transition 32,33 of W between the amorphous phase and the crystalline bcc phase 9,16 . When the underlayer thickness is larger than d C , the SMR ( Fig.…”
mentioning
confidence: 99%
“…However, for the critical dimension lower than tens of nanometer, it is reported that the resistivity of Cu is increased sharply due to the size effect related to the long electron mean free path (EMFP) of 39 nm in addition to the decreased reliability of Cu as the device operating temperatures and current densities are increased . As one of possible replacements of Cu, W, which is widely used as an interconnect layer, a diffusion barrier of semiconductor integrated circuits, a gate material for 3D NAND flash memory, etc is investigated for the next generation interconnection material because of the smaller EMFP of 19 nm and a high melting point (3,695 K compared with Cu of 1,357 K) . Since W has a smaller EMFP than Cu, it is expected to reduce the size effect of surface scattering and grain boundary scattering as it goes to nanometer dimension …”
Section: Introductionmentioning
confidence: 99%
“…As one of possible replacements of Cu, W, which is widely used as an interconnect layer, a diffusion barrier of semiconductor integrated circuits, a gate material for 3D NAND flash memory, etc is investigated for the next generation interconnection material because of the smaller EMFP of 19 nm and a high melting point (3,695 K compared with Cu of 1,357 K) . Since W has a smaller EMFP than Cu, it is expected to reduce the size effect of surface scattering and grain boundary scattering as it goes to nanometer dimension …”
Section: Introductionmentioning
confidence: 99%